FEATURES OF PUBLIC HEALTH COVERNMENT REGULATION IN THE CARPATHIAN REGION AS A PART OF POLAND (THE SECOND POLISH REPUBLIC) IN 1919-1939 - Soroka, O.Ya. (World of Medicine and Biology, 2018)
Based on the archival, published historical documents and other available information sources, the specifics of public health state regulation in the Carpathian region as part of Poland (1919-1939 years II) (II Rzecz Pospolita, Polish - II Rzeczpospolita, Polska) is found to be a relevant experience for building a modern healthcare system in Ukraine .The change of various socio-economic formations, the Carpathian region’s transfer from the influence of one to another country, significantly influenced the nature of social relations in the region, including health care. It was established that the authorities and public institutions in the field of health care while the Carpathian region being a part of Poland in 1919-1939, in an effort to expand medical care and educational work among the population, in order to prevent diseases and increase life expectancy, started a systematic purposeful work on forming the prevention medicine system and in fact laid the first bricks in the sphere of public health. Their experience and practice is not only of scientific interest, but will also have practical significance for construction of a modern health care system.
Keywords: government regulation; public health; Carpathian region; Poland